Feature based cost and carbon emission modelling for wire and arc additive manufacturing - Guo, Jianing (Cranfield University, 2012)
The wire and arc additive manufacturing (WAAM) is a CNC and welding deposition based additive manufacturing method. This novel manufacturing technique has potential cost and environment advantage and was developed as an ideal alternative for industrial sustainable development. The aim of this project is to develop a cost and carbon emission model primarily for the WAAM manufacturing cost (£) calculation and secondly for the WAAM carbon emission (KgCO2e) estimation, which can be used by the decision makers and design engineers in product design stage without detailed process information. Literature review and an industry survey were carried out first to capture the overview of this research context and the essential data for cost modelling. Then the cost breakdown structure (CBS) and cost drivers were determined. Thereafter, a feature based cost model and detailed cost equations were developed. A specific Greenhouse Gases (GHG) emission model was also established which follows the specification of existing carbon footprint measurement standards. As part of this project, an integrated software tool was developed by using MS Visual Basic language. The proposed cost and GHG emission model were implemented in this software. With the ability of directly capture geometry data from CAD files and fully automatic calculation, the software tool is efficient and convenient. Three case studies were conducted to demonstrate the proposed cost model and software tool. The comparative cost analyses with other conventional manufacturing methods were also discussed in these case studies. Finally, the capacity and reliability of the cost software were validated by experts from industry and academia. The implementation of the research outcomes of this project can achieve accurate early cost estimation for WAAM conveniently. Moreover, it can clarify the cost and environment advantage of WAAM and assist to identify the most suitable situation for adopting WAAM from a cost and sustainable point of view.
Keywords: WAAM; cold metal transfer; cost estimation; GHG emission; CATIA automation